Comprehensive RNA-seq analysis of benign prostatic hyperplasia (BPH) in rats exposed to testosterone and estradiol - Xiao-Hu Tang; Zhi-Yan Liu; Jing-Wen Ren; Heng Zhang; Ye Tian; Jian-Xin Hu; Zhao-Lin Sun; Guang-Heng Luo (Scientific Reports)
Abstract The imbalance between estrogen and androgen may be an important mechanism of BPH, but the specific mechanism remains unclear. We used mixed sustained-release pellets made of testosterone and estradiol (T + E2) to stimulate the establishment of a BPH rat model. Compared to the prostate hyperplasia rat model using only androgens, the new prostate hyperplasia rat model can be observed to have better macroscopic and pathological characteristics of prostate hyperplasia. We used RNA-seq and bioinformatics to detect differentially expressed genes (DEGs) between the prostate tissue of the novel benign prostatic hyperplasia rat group and the control group, including 458 DEGs, of which 336 were upregulated and 122 were downregulated. Then, RT-qPCR confirmed the authenticity of sequencing results. The analysis results showed that Kif4a and Mki67 were the top core genes in the PPI network. Moreover, we found that these two genes have a positive correlation with each other in multiple cancer tissues, normal tissues, and cancer cells. The DEGs were mainly involved in mitotic nuclear division, nuclear chromosome segregation, and cytokine cell receptor interactions. DEGs were also regulated by 250 miRNAs. In conclusion, we built a novel T + E2-induced rat BPH model, and discovered potentially important genes, pathways, and miRNA-mRNA regulatory networks.